2022
DOI: 10.1155/2022/6925772
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation, Metastasis, and Radiosensitivity of Nasopharyngeal Carcinoma Cells in the Expression and Effect of Kiwifruit Extract through the Regulation of miR-205-5p

Abstract: Background. Radix Actinidiae extract (RAE) has been shown to inhibit cancer in many studies, but its potential mechanism in nasopharyngeal cancer (NPC) progression remains unclear. Methods. NPC cells (SUNE1) were treated with different doses of RAE. For transfection, SUNE1 cells were transfected with the microRNA (miR)-205-5p inhibitor (anti-miR-205-5p) or mimic followed by treatment with 200 μg/mL RAE for 24 h. The MTT assay and colony formation assay were used to detect cell proliferation and radiosensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…For instance, miR-29c [35], miR-22 [36], miR-142-3p [37], and PD-L1 [38] can predict the prognosis and tumor-free survival rate of NPC patients; miR-23a, DAKP1, GRP78, and 14-3-3 sigma can assess the sensitivity of radiotherapy [39]. Kiwi fruit extract has been found to regulate miR-205-5p, resulting in the modulation of proliferation, metastasis, and radiosensitivity of nasopharyngeal carcinoma cells [40]. Our study found that miR-205-5p and TP53INP1 were involved in curcumin-mediated effects on the biological functions of C6661-IR, and the former directly targeted the latter.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-29c [35], miR-22 [36], miR-142-3p [37], and PD-L1 [38] can predict the prognosis and tumor-free survival rate of NPC patients; miR-23a, DAKP1, GRP78, and 14-3-3 sigma can assess the sensitivity of radiotherapy [39]. Kiwi fruit extract has been found to regulate miR-205-5p, resulting in the modulation of proliferation, metastasis, and radiosensitivity of nasopharyngeal carcinoma cells [40]. Our study found that miR-205-5p and TP53INP1 were involved in curcumin-mediated effects on the biological functions of C6661-IR, and the former directly targeted the latter.…”
Section: Discussionmentioning
confidence: 99%